Objective transmission cost allocation based on marginal usage of power network in spot market. (June 2020) - Yang, Zhifang; Lei, Xingyu; Yu, Juan; Lin, Jeremy
Highlights: A method for determining the marginal usage of the power network is introduced. The impact of loss modeling on the marginal usage of the power network is investigated. An objective method of transmission cost allocation is presented. Abstract: Transmission cost allocation is important for a liberalized market with open access to transmission facilities. However, it remains controversial how to objectively allocate the transmission costs because there is no unique answer for the mapping between the power injections at buses and the power flows on branches. However, the marginal usage of the power network can be uniquely determined according to the market-clearing solution. In this paper, an objective transmission cost allocation method is proposed based on the marginal usage of the power network. The influence of the loss modeling on the proposed method is discussed. The "extent of use" of transmission facilities is determined based on the economic principles without subjective assumptions, which obeys the fairness requirement of spot markets. The proposed method is computationally efficient, in which only matrix manipulations are involved. Moreover, the proposed approach is compatible with the standards and procedures of the current spot market operation in the U.S., China, and many other countries and holds promise for industrial applications.